Localization and Perturbations of Roots to Systems of Polynomial Equations - Michael Gil' (International Journal of Mathematics and Mathematical Sciences)
We establish estimates for the sums of absolute values of solutions of a zero-dimensional polynomial system. By these estimates, inequalities for the counting function of the roots are derived. In addition, bounds for the roots of perturbed systems are suggested.